FORMULASI KEBIJAKAN RETRIBUSI JASA USAHA DI KABUPATEN KUTAI KARTANEGARA - Santi Maryana; Heryono Susilo Utomo; Enos Paselle (Magister Administrasi Publik FISIP Universitas Mulawarman, 2021)
Kutai Kartanegara Regency has just passed Perda No.16/2016 Busines Service Charge and this research is aimed at knowing the policy formulation process and the factors that influence it. This research uses descriptive qualitative methods, with interactive data analysis tools. Based on the results of the study, it was found that the main problem in the formulation of Perda No.16/2016 is stillthe contribution of local user fees, especially those that come from business services fees. At the stage of the policy agenda, it is important to increase revenue from the regional levies sector to reduce dependence on revenue sharing from oil, gas dan local. At the stage of selecting alternative policies, there are interests and various reasons such as a lack of political will and high budgets for investment in supporting infrastructure. At the stage of determining the policy, the majority of DPRD factions support the stipulation of the Raperda on Business Services Retribution to become a Regional Regulation, although during the discussions process there is often a tug of war between the factions int the DPRD. The education, experience and data and information factors affect the formulation of Perda no. 16/2016, it is just that it is no longer an inhibiting factor because it has been overcome by the prensence of an Expert Team, a workshop or training to increase the capacity of the DPRD and the Executive Division. The Factors inhibiting the formulation of Perda No. 16/2016 are political factors and budget support.Keywords : Formulation, Regional Regulations, Business Service Retribution